2015
DOI: 10.3906/vet-1409-24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-level chromium methionine supplementation in lambs fed a corn-based diet on the carcass characteristics and chemical composition of the longissimus muscle

Abstract: One of the main goals of the feedlot industry is to increase efficiency in the final stages of fattening. Therefore, the use of modulators of growth (hormones and beta-agonist agents) is widespread. The concern about the potential impact of the use of these growth promoters has furthered interest in the search for safe alternatives of modulating agents of growth in recent years. In this regards, the use of chelated minerals has shown interesting advantages in nonruminant species. In this sense, chromium (Cr) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
3
1
0
3
Order By: Relevance
“…The results agreed with the researcher Soumar et al (2020), as he did not get significant differences between treatments in the final weight characteristic when different levels of Cr-Met and Zn-Met were used. The results also agreed with Sanchez-Mendoza et al (2015) when Cr-Met was used. In feeding lambs, no significant differences were found between the treatments.…”
Section: Results and Discussion: Final Weightsupporting
confidence: 79%
See 2 more Smart Citations
“…The results agreed with the researcher Soumar et al (2020), as he did not get significant differences between treatments in the final weight characteristic when different levels of Cr-Met and Zn-Met were used. The results also agreed with Sanchez-Mendoza et al (2015) when Cr-Met was used. In feeding lambs, no significant differences were found between the treatments.…”
Section: Results and Discussion: Final Weightsupporting
confidence: 79%
“…The results in Table (3) indicate that there were no significant differences between the first and second periods (129.19, 110.17) g, respectively, in the rate of daily weight gain, and the results also did not show any significant differences between the first, second, third and fourth treatments (138.56, 108.03, 131.06 101.06 ) gm, respectively, while the third treatment in the first period (164.99) gm was significantly superior at (P≤0.05) over the second, third and fourth treatments (91.42, 97.14, 99.28) gm, respectively for the second period, and the first and second treatments did not record any significant difference in daily weight gain. These results agreed with researchers Soumar et al (2020) and Sanchez-Mendoza et al (2015) when they used different levels of Cr-Met they found no significant differences between treatments. These results differed with Alimohamady et al (2019) and Jafarpour et al (2015), as they obtained significant differences between treatments when they used Zn-Met at different levels.…”
Section: Average Daily Weight Gainsupporting
confidence: 91%
See 1 more Smart Citation
“…They are highly reactive to cell organelles e.g. polyunsaturated fatty acids, proteins and nucleic acid (Sánchez-Mendoza et al, 2015). Metals like Cr are very reactive and induce oxidative damage by generating reactive oxygen species (ROS) .…”
Section: Introductionmentioning
confidence: 99%
“…Existem informações variáveis a respeito da influência da suplementação com Cr nas características de carcaça e qualidade de carne em ruminantes. No entanto, diversos estudos relataram que a suplementação com Cr influencia o rendimento de carcaça através do aumento do peso do músculo longissimus e da área de olho de lombo na altura da 12ª costela, em cordeiros em fase de terminação (DOMÍNGUEZ-VARA et al, 2009;ARVIZU et al, 2011;ESTRADA-ANGULO et al, 2013;SÁNCHEZ-MENDOZA et al, 2015). (BERNHARD et al, 2012) Pode ser encontrada nos mamíferos, nas células musculares.…”
Section: Parâmetros De Carcaça E Qualidade De Carneunclassified